2019
DOI: 10.1111/lang.12332
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Children's Understanding of Complex Syntax: A Comparison of Two Methods

Abstract: We examined the effect of two methods of assessment—multiple‐choice sentence–picture matching and an animated sentence‐verification task—on typically developing children's understanding of relative clauses. A sample of children between the ages of 3 years 6 months and 4 years 11 months took part in the study (N = 103). Results indicated that (a) participants performed better on the sentence‐verification than on the multiple‐choice task independently of age, (b) each testing method revealed a different hierarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(68 citation statements)
references
References 46 publications
5
61
0
2
Order By: Relevance
“…With respect to children with typical development, we can see that they performed near ceiling on all relative clause types. In a previous study ( Frizelle et al , 2018a ), reporting on typically developing 3- to 5-year-olds, we reported the following hierarchy: intransitive subject > indirect object = transitive subject = object = oblique relatives (where ‘>’ refers to significantly greater than, and ‘=’ refers to no significant differences). However, the children included in the current study are considerably older, ranging in age from 5;01 to 7;09 years and we therefore expect a more stable performance across relative clause types.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…With respect to children with typical development, we can see that they performed near ceiling on all relative clause types. In a previous study ( Frizelle et al , 2018a ), reporting on typically developing 3- to 5-year-olds, we reported the following hierarchy: intransitive subject > indirect object = transitive subject = object = oblique relatives (where ‘>’ refers to significantly greater than, and ‘=’ refers to no significant differences). However, the children included in the current study are considerably older, ranging in age from 5;01 to 7;09 years and we therefore expect a more stable performance across relative clause types.…”
Section: Resultsmentioning
confidence: 78%
“…In this analysis we calculated the proportion of children in each group that passed each construction on the sentence verification task (shown in Table 8 ), where a pass was defined as a score of 7 or 8 out of 8 items correct. This allowed us to document the order of difficulty of the different complex sentence types in the three groups and to consider if the relative clauses followed the same rank ordering as was observed in our prior study of TD 3- to 5-year-olds ( Frizelle et al , 2018a ). An analysis of Table 6 shows that within each type of complex sentence (relative, adverbial, complement), all three groups performed best on relative clauses, while children’s performance on adverbial and complement clauses was similar within each group.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations